Current genetic conservation of Chinese indigenous horses revealed with Y-chromosomal and mitochondrial DNA polymorphisms. Issue 2 (19th February 2021) - Liu, Shuqin; Fu, Chunzheng; Yang, Yunzhou; Zhang, Yuanyuan; Ma, Hongying; Xiong, Zhiyao; Ling, Yao; Zhao, Chunjiang
Abstract: To investigate the genetic diversity of Chinese indigenous horses and determine the genetic status of extant horse breeds, novel Y chromosomal microsatellite markers and known Y chromosomal SNPs and mtDNA loop sequences, were employed to study the genetic diversity levels of 13 Chinese indigenous horse populations and four introduced breeds. Sixteen Y-chromosomal microsatellite markers, including seven newly identified loci, were used in the genotyping. The results showed that 4 out of the 16 loci were highly polymorphic in Chinese indigenous horse populations, in which the polymorphisms of 3 loci, ECAYP12, ECAYP13, and ECAYCAU3, were first reported in the present study. The polymorphic Y chromosomal microsatellite markers result in 19 haplotypes in the studied horses and formed 24 paternal lines when merged with the 14 Y chromosomal SNPs reported previously. The haplotypes CHT18 and SS24 harboring AMELY gene mutation were the ancestral haplotypes, and other haplotypes were derived from them by one or more mutation steps. The horse populations in mountainous and remote areas of southwestern China have the most ancient paternal lines, which suggests that ancient paternal lines preserved in local populations attributed to less human interventions. Our results also showed that the northern local breeds had higher mtDNA diversity than the southern ones in China. The frequency of haplogroup B, F, and G of mtDNA in Chinese indigenous horses has declined in recent years, and some breeds are in endangered status mainly due to small population sizes. Urgent actions should be taken to conserve the genetic diversity of the indigenous horse populations, especially the rare paternal lines. Our findings help to elucidate the genetic diversity and evolutionary history of Chinese domestic horses, which will facilitate the conservation of the indigenous horses in the future.